The Impact Of Fiscal And Monetary Policy On Economic Performance - triansyah, Fadli agus; Gunawan, Ashari; Ramadhaniyati, Resti (Jurnal Ekonomika Dan Bisnis (JEBS), 2022)
This study aims to analyze and determine the effect of: (1) government spending on economic growth in Indonesia, (2) taxes on growth in Indonesia, (3) money supply on economic growth in Indonesia and (4) interest rates on economic growth . This study used the Ordinary Least Squared (OLS) analysis tool method. The dependent variable in this study is economic growth. While the independent variables in this study are government spending, taxes, money supply and interest rates. The results of the study conclude that (1) government spending has a significant and positive effect on economic growth in Indonesia. (2) taxes have a significant and positive effect on economic growth in Indonesia. (3) the money supply also has no positive effect on economic growth in Indonesia. (4) interest rates have no effect on economic growth in Indonesia and are negative. Based on these results, the policy that can be suggested by the Government of Indonesia is the need for local government efforts or policy makers to increase government spending (Fiscal Expansion Policy). The government is expected to be able to regulate the appropriate tax allocation so as not to undermine consumers' purchasing power. Central Government and Bank Indonesia in order to maintain liquidity or availability of money in the economy in Indonesia. The government together with the banking sector, especially Bank Indonesia, should maintain a healthy interest rate so that it does not have an impact on reducing investor interest in investing.